The analytic hospitality executive : implementing data analytics in hotels and casinos - McGuire, Kelly Ann (Wiley and SAS business series, 2017)
"This book will help decision makers within the hospitality/gaming industries understand big data and analytics as they apply to their industry. It will provide practical tips for incorporating analytics into existing business processes as well as assist managers discover where they can drive value in their organization via advanced analytics. The book will also contain tips and tools for creating a strategic analytic culture as opposed to silos of analytic competence and it will help identify which data sources will provide value to their organization and how to turn that information into insights"--